Low seroprevalence of COVID-19 among healthy Malaysian residents in Kepala Batas, Pulau Pinang, Malaysia, during the fourth pandemic wave - Zainudeen, Zarina Thasneem; Hashim, Ilie Fadzilah; Azman, Nur Adila; Abdullah, Firdaus Hakimi; Abu Bakar, Firdaus Farhani; Rasit, Rasiah; Ismail, Intan Hakimah; Abdullah, Baharudin; Husain, Salina; Palaniappan, Sp; Kassim, Shahjahan; Woo, Kent; et al. (Universiti Putra Malaysia Press, 2024)
Introduction: Seroprevalence studies on COVID-19 in a general population, including those who are asymptomatic, is important to understand the extent of undetected transmission in a defined community. Method: This is a cross-sectional, population-based study and was conducted among healthy Malaysian community in Kepala Batas, Penang, from November 2020 to September 2021. Antibodies to SARS-CoV-2 were detected using Healgen COVID-19 IgG/IgM Rapid Test Cassette. Result: A total of 422 respondents from Kepala Batas, Penang, were recruited for this cross-sectional study. From the total, three hundred and eighty (380) healthy individuals from the were selected and analysed. The mean age of the respondents was 33 ± 14.23 years old, with more female respondents and most respondents were Malay (95.8%). A total of 21 (5.5%) respondents were found to have positive COVID-19 antibodies. Among them, two were (0.5%) IgM positive, while nineteen (5.0%) were IgG positive. Conclusion: The seroprevalence of antibodies against SARS-CoV-2 among possible cases was lower than expected. Malaysian Journal of Medicine and Health Sciences (2024) 20(SUPP3):1-5. doi:10.47836/mjmhs20.s3.1